Education for polyarchy: a new pa challenge - Olshfski Dorothy; Cunningham Robert B.
Resource constraints, citizen activism, and the threat of privatization are driving public organizations toward responsiveness and efficiency. Hierarchy is giving way to polyarchy in the administrative system. an interactiv classroom which uses analysis and feedbank to leverage the students' experiences in management situations can prepare public administration students for this new polyarchal work environment
Keywords: Public Administration -- Study And Teaching